Protecting Significant and Sensitive Facilities - Toyama, Masato; Sagara, Junko; Ishiwatari, Mikio (World Bank, Washington, DC, 2013)
The Great East Japan Earthquake (GEJE) was a multi-hazard event. A massive quake triggered a series of tsunamis of unprecedented dimension, as well as the subsequent nuclear accident. Sensitive facilities need to be protected against low-probability and complex events because damage to such facilities can have a cascading effect, multiplying the destruction and leading to irreversible human, social, economic, and environmental impacts. This report gives findings; lessons; and recommendations for developing countries.